GENERAL PEDAGOGICAL KNOWLEDGE OF AUSTRIAN TEACHERS. - DITTRICH, ANN-KATHRIN (Studia Archaeologica Brunensia, 2020)
General pedagogical knowledge (GPK), as teachers' basic professional knowledge, has a significant influence on sustainable learning and teaching. Rapidly accelerated processes of change encourage teachers to reflect on their GPK. The aim of this paper is to discuss the current understanding of Austrian teachers' GPK in their everyday school practices and point out the challenges they experience. The study is based on a qualitative reconstructive approach that involves interviews and observations. Previous findings have shown that a reconstructive approach provides an understanding that complements existing studies and conceptualizations of GPK. The study also presents further outcomes in terms of the central meaning of interactional processes, a student orientation, and factors and challenges that influence GPK. The challenges involve in particular the requirements raised by current transformation processes and emphasize the necessity of a continuous process of professional learning.